2015
DOI: 10.1002/adma.201503869
|View full text |Cite
|
Sign up to set email alerts
|

Injectable 2D MoS2‐Integrated Drug Delivering Implant for Highly Efficient NIR‐Triggered Synergistic Tumor Hyperthermia

Abstract: MoS2 nanosheets and a doxorubicin (DOX)-containing poly (lactic-co-glycolic acid) (PLGA)/MoS2 /DOX composite implant are successfully constructed based on the unique phase-changing behavior of PLGA/MoS2 /DOX oleosol within tumors. The fast phase transformation can firmly restrict MoS2 and DOX within tumors, and the integrated MoS2 and DOX can endow the implant with high synergistic photothermal and chemotherapeutic efficiency against tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
153
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(162 citation statements)
references
References 25 publications
0
153
0
Order By: Relevance
“…10 days later, mice were divided into two groups (n=8) randomly as reported [35]. Magnolol (25 mg/kg) was injected intraperitoneally every other day.…”
Section: Methodsmentioning
confidence: 99%
“…10 days later, mice were divided into two groups (n=8) randomly as reported [35]. Magnolol (25 mg/kg) was injected intraperitoneally every other day.…”
Section: Methodsmentioning
confidence: 99%
“…An updated overview on the development of new photosensitizers for anticancer photodynamic therapy was reported by Zhang et al, [30]. More clinical studies of the efficacy of PDT and PTT using various nanoparticles have been reported [31][32][33][34][35][36][37][38][39].…”
Section: Discussion Of Combined Ptt and Pdtmentioning
confidence: 99%
“…[225] Under 808 nm (1 W cm −2 ) light irradiation, the MoS 2 and DOXfilled PMD implant displayed temperature rise of 30.2°C and www.advancedsciencenews.com www.advtherap.com induced rapid DOX release from 8.7% to 31.8% in 5 min. [225] Under 808 nm (1 W cm −2 ) light irradiation, the MoS 2 and DOXfilled PMD implant displayed temperature rise of 30.2°C and www.advancedsciencenews.com www.advtherap.com induced rapid DOX release from 8.7% to 31.8% in 5 min.…”
Section: Photothermal Therapy and Drug/gene Deliverymentioning
confidence: 99%
“…Overall, this strategy may allow a reduction in doses of iron oxides, magnetic field strength, and NIR excitation power to comply with in vivo settings. TiO 2-x treatment with 808 nm (1 W cm −2 ) irradiation www.advancedsciencenews.com www.advtherap.com MoS 2 Exfoliation Chitosan 80 nm (l) 4-6 nm (t) -PTT, drug delivery, CT imaging [187] MoS 2 Exfoliation -14.7 nm (hd) -PDT, down-and upconversion fluorescence Imaging [188] MoS 2 Exfoliation LA-PEG 50 nm (l) 2 nm (t) 28.4 L g −1 cm −1 at 800 nm PTT, drug delivery [191] MoS 2 Exfoliation BSA 89 nm (l) 5-15 nm (t) -PTT, drug delivery [192] MoS 2 Ionic liquid grinding Chitosan 120 nm (l) 1.4 nm (t) 62.6 L g −1 cm −1 at 800 nm PTT [194] MoS 2 Solvothermal PEG 79.2 nm (l) 0.29 nm (t) -PTT [197] MoS 2 Exfoliation -0.8 µm (l) 1.6 nm (t) 29.2 L g −1 cm −1 at 800 nm PTT [199] MoS 2 Solvothermal LA-PEG 90 nm (l) -PTT [201] MoS 2 Hydrothermal Polyacrylic acid LA-PEG 90 nm (l) -PTT [203] MoS 2 Sonication BSA 181 ± 3 nm (l) (hd) 10.65 nm (t) -PA imaging [209] MoS 2 Exfoliation DMSA-IONP-PEG-Amine LA-PEG 50-200 nm (l) -PTT, PA, MRI, and PET imaging [211] MoS 2 Hydrothermal Fe 3 O 4 PEG 190.1 nm (hd) -PTT, PA, and MRI imaging [213] MoS 2 Solvothermal Polyaniline PEG 21.5 ± 3.9 nm (hd) -PTT, RT, PA, and CT imaging [215] MoS 2 Exfoliation PEG-amine Mesoporous silica DOX 450 nm (hd) -PTT, drug delivery [223] MoS 2 Exfoliation PEI-HA DOX NOTA-64 Cu 30-50 nm (l) 5-7 nm (t) -PTT, drug delivery [224] MoS 2 Solvothermal PLGA oleosol DOX 100 nm (l) -PTT, drug delivery [225] MoS 2 Exfoliation LA-PEG PEI 90 nm (hd) -PTT, gene delivery [226] MoS 2 Exfoliation LA-PEI SH-PEG 100-150 nm (l) 6-8 nm (t) -PTT, gene delivery [227] MoS 2 Hydrothermal Gen 5 polyamidoamine (PAMAM) 420 nm (hd) -PTT, gene delivery [230] MoS 2 Exfoliation LA-PEG 100 nm (hd) 28.4 L g −1 cm −1 at 800 nm PTT, PDT, and PA imaging [231] MoS 2 Hydrothermal PEI Fe 3 O 4 ICG Pt(IV) 80 nm (hd) -PTT, PDT, PA, MRI imaging [234] WS 2 Exfoliation LA-PEG 3 ± 0.18 nm (l) -PTT, RT, PA, and CT imaging [179c] WS 2 Exfoliation BSA 20-100 nm (l) 4-5 nm (t) 21.8 L g −1 cm −1 at 808 nm PTT, PDT, and CT Imaging [186] WS 2 Exfoliation LA-PEG 50-100 nm (l) 1.6 nm (t) 23.8 L g −1 cm −1 at 808 nm PTT, PA, and CT imaging [189] WS 2 High-temperature reaction Gd 3+ C 18 PMH-PEG 90-100 nm (hd) 22.6 L g −1 cm −1 at 808 nm PTT, ...…”
Section: Metal Oxidesmentioning
confidence: 99%